[Close-Up of Sod-Brick Construction at Glaumbur] - Streng, Evelyn Fiedler (1975)
Photograph of a close-up of a sod-brick construction at Glaumbur in Iceland. The brown, dirt mounds covered in green grass form roofs for buildings. A white, rectangular window sits in the hill to the left, surrounded by a dirt frame. A cross pattern creates a wall in the mound to the right.